2016
DOI: 10.1016/j.thromres.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of venous thromboembolism in patients with non-Hodgkin lymphoma

Abstract: Introduction Patients with non-Hodgkin lymphoma (NHL) have an increased risk of venous thromboembolism (VTE). Current risk-prediction models classify NHL as a single entity. We aimed to quantify the difference in VTE risk in follicular lymphoma (FL) versus diffuse large B cell lymphoma (DLBCL). Methods Using a prospective cohort study, we identified 2,730 patients (2,037 DLBCL; 693 FL) within the Veteran’s Administration Central Cancer Registry. A competing risk model assessed the association between VTE ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
52
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 38 publications
4
52
0
4
Order By: Relevance
“…Patients as those with low-grade histology who did not require a hospital stay were not retrieved. As expected, this may explain the higher incidence rate of VTE with respect to other reports 1,2,8,10 . Therefore, our study tackles the issue of VTE frequency in a population at increased risk, in whom special care is required and specific information are needed.…”
supporting
confidence: 76%
See 2 more Smart Citations
“…Patients as those with low-grade histology who did not require a hospital stay were not retrieved. As expected, this may explain the higher incidence rate of VTE with respect to other reports 1,2,8,10 . Therefore, our study tackles the issue of VTE frequency in a population at increased risk, in whom special care is required and specific information are needed.…”
supporting
confidence: 76%
“…The VTE risk is the highest upfront during the first month after lymphoma diagnosis and decreases over time 2 . This upfront risk may be related to tumor burden and start of chemotherapy as contributing factors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with non‐Hodgkin lymphoma (NHL), particularly those with aggressive lymphoma, those with a higher stage of disease (stage III or IV), and those with central nervous system involvement at diagnosis, are at high risk for venous thromboembolism (VTE) . Several studies in patients with NHL have shown that VTE events occur soon after the NHL diagnosis and during chemotherapy administration . However, in the majority of these studies, patients were followed for only 1 to 3 years, and this has left a gap in our understanding of the long‐term risk of VTE.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Several studies in patients with NHL have shown that VTE events occur soon after the NHL diagnosis and during chemotherapy administration. 1,[4][5][6] However, in the majority of these studies, patients were followed for only 1 to 3 years, and this has left a gap in our understanding of the long-term risk of VTE. Furthermore, blood or marrow transplantation (BMT) is increasingly being used successfully for relapsed or refractory NHL.…”
Section: Introductionmentioning
confidence: 99%